Investigation Of Serum Level Of T4, TSH, Free Testosterone And Prolactin Hormones As Well As Alb And SHBG Proteins In Women With Hair Loss Vs. Those Without Hair Loss - Anahita Moaven; Farzaneh Moghaddam; Masomeh Arabshahi; Mohammad Ali Hafezi; Masomeh Khoshgam; Ladan Hosseini Gohari (Tehran University of Medical Sciences, 2013)
Background and Aim: Female pattern hair loss(female androgenic alopecia) is a common but puzzling condition in women which increases by aging. Female hair loss is strongly linked to hormones and hormonal imbalances. The aim of this study was to determine the serum level of hormones such as T4, TSH, free testosterone, Prolactin(PRL) and Alb, SHBG in women(15-50 years old) with hair loss versus those without hair loss. Materials and Methods: In this cross-sectional case-control study, 71 women with hair loss and 70 normal women were selected from skin and hair care day clinics. The level of hormones and SHBG were measured by ELISA, and Alb was measured by spectrophotometery. Data were analyzed by independent t-test. Results: After analyzing the data and determining the levels of TSH, T4, Prolactin, Alb, SHBG, no significant difference was found between the case and control groups. However, free Testosterone level was significantly different between patients and controls(P= 0.000), with a higher mean level in the case group(patients). Conclusion : Since androgens have a major role in regulating the biological cycle of hair in women and since there was a significant difference between free testosterone in patient and control groups, we suggest that the serum level of free testosterone should be measured in women with androgenic alopecia .